I Can't Forget about U: Lifetime Unemployment and Retirement Well-Being - Andrew E. Clark; Anthony Lepinteur (Institute of Labor Economics (IZA), 2024)
It is well-known that unemployment leaves scars after re-employment, but does this scarring effect persist even after retirement? We analyse European data on retirees from the SHARE panel, and show that the well-being of the retired continues to reflect the unemployment that they experienced over their working life. These scarring effects are somewhat smaller for older retirees, but larger for those who arguably had higher expectations regarding the labour market when they were active. Despite the substantial variation in culture and labour-market institutions over the 29 countries in our sample, there are no significant country differences. This long-run scarring for those who have left the labour market underlines that contemporaneous correlations significantly under-estimate the well-being cost of unemployment.
Keywords: J21; J63; I31; 330; unemployment; retirement; scarring; CASP; SHARE